Dual-Hop N-Relay Assisted Transmission for IDMA Systems over Weibull Fading Channels - Bilim, Mehmet; Kapucu, Nuri; Develi, Ibrahim (Elektronika ir Elektrotechnika, 2015)
This paper proposes and investigates dual-hop N-relay assisted transmission scheme for interleave-division multiple access with decode-and-forward relaying. In the considered system, chip-by-chip detection method is employed to suppress multiuser interference at relay and destination nodes. We assumed binary phase shift keying modulation and analyse the system under study in terms of bit error rate when the source-relay and relay-destination links experience Weibull fading. Our simulation results show that the dual-hop N-relay assisted decode-and-forward relaying can be a promising alternative for the performance improvement of interleave-division multiple access by efficiently mitigating the multiuser interference at the relay nodes as well as destination node. DOI: http://dx.doi.org/10.5755/j01.eee.21.4.12787